Pemberdayaan Kelompok Wanita Tani Desa Bakipandeyan Sukoharjo Menuju Kesejahteraan Keperempuanan - Firstnandiar Glica Aini Suniaprily; Daniyel Dwi Ardiyanto; Arneta Indah Noorlintang Mentari; Alwan Fauzan; Afrigh Alaina Shobron; Ada Riski Rahma Noviana; Amilia Febriani; Yulian Dwi Nurwanti; Adhy Nugraha (Publikasi Inspirasi Indonesia, 2024)
This service has the aim of empowering in the field of agriculture which is focused on farm women's groups located in Bakipandeyan Village, Baki District, Sukoharjo Regency, this empowerment program targets women's welfare for members of farm women's groups in Bakipandeyan Village. The purpose of this research is to find out the empowerment of KWT in Bakipandeyan Village, Baki Subdistrict, Sukoharjo Regency, and is expected to add to the literature study, especially social science for further research. For Government Interests This research is expected to contribute in the form of ideas and ideas as well as input in an effort to improve KWT empowerment in Bakipandeyan Village, Baki District, Sukoharjo Regency based on an empirical theoretical basis. For future researchers, this research can be used as material for consideration or can be further developed, as well as a reference to similar research.